2021
DOI: 10.1093/cid/ciab361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Messenger RNA Coronavirus Disease 2019 (COVID-19) Vaccines Against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in a Cohort of Healthcare Personnel

Abstract: In a large cohort of US healthcare personnel (HCP) without prior COVID-19 infection, 94,382 doses of mRNA COVID-19 vaccine were administered to 49,220 individuals. The adjusted vaccine effectiveness following two doses of each of the two available brands of mRNA vaccine exceeded 96%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 9 publications
3
86
1
2
Order By: Relevance
“…Recent data from the CDC showed that the widely used mRNA vaccines in the US reduce the infection risk by 91% and data from different groups confirm that breakthrough infections after full vaccination are scarce (9)(10)(11). Data also show that vaccines reduce symptomatic and asymptomatic infections (12)(13)(14). Our data is consistent with published data, and even though the total number of infections after vaccination is not known, the occurrence of positives after full vaccination in our surveillance cohort has been infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the CDC showed that the widely used mRNA vaccines in the US reduce the infection risk by 91% and data from different groups confirm that breakthrough infections after full vaccination are scarce (9)(10)(11). Data also show that vaccines reduce symptomatic and asymptomatic infections (12)(13)(14). Our data is consistent with published data, and even though the total number of infections after vaccination is not known, the occurrence of positives after full vaccination in our surveillance cohort has been infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…** Even though FDA-authorized vaccines are highly effective, breakthrough cases are expected, especially before population immunity reaches sufficient levels to further decrease transmission. However, vaccine breakthrough infections occur in only a small fraction of all vaccinated persons and account for a small percentage of all COVID-19 cases (5)(6)(7)(8). The number of COVID-19 cases, hospitalizations, and deaths that will be prevented among vaccinated persons will far exceed the number of vaccine breakthrough cases.…”
mentioning
confidence: 99%
“…CDC will continue to lead studies in multiple U.S. sites to evaluate vaccine effectiveness and collect information on all COVID-19 vaccine breakthrough infections regardless of clinical status. Additional information and resources to help public health departments and laboratories investigate and report COVID-19 vaccine breakthrough cases are available at https://www.cdc.gov/vaccines/covid-19/ health-departments/breakthrough-cases.html.FDA-authorized COVID-19 vaccines are safe and effective(1)(2)(3)(4)(5)(6)(7)(8). CDC recommends that all persons aged ≥12 years be vaccinated with an FDA-authorized COVID-19 vaccine ¶ ¶ (10).…”
mentioning
confidence: 99%
“…Vaccines have shown an early impact on the "domino effect" of the SARS-CoV-2 infection. Several studies provided strong short-term evidence that vaccinating HCWs can substantially reduce symptomatic and asymptomatic SARS-CoV-2 infection and, therefore, might help to reduce transmission of infection in the healthcare settings [5][6][7][8][9][10][11][12]. In this retrospective cohort study, vaccination with two doses of the authorized available mRNA vaccines was associated with a signi cantly lower incidence rate for symptomatic SARS-CoV-2 infection in HCWs.…”
Section: Discussionmentioning
confidence: 89%
“…In general, people are considered fully vaccinated two weeks after their second dose in a 2-dose series, such as the P zer or Moderna vaccines, or two weeks after a single-dose vaccine, such as Johnson & Johnson's Janssen vaccine [2]. Data on mRNA vaccine effectiveness for HCWs, who are frequently at risk of exposure to SARS-CoV-2, has been consistent with the results from the phase 3 randomized clinical trials of the mRNA vaccines, which showed e cacy against symptomatic SARS-CoV-2 infection around 95% [3][4][5][6][7][8][9][10][11][12]. Authorized vaccines are not 100% effective at preventing symptomatic and asymptomatic infections, but they are effective, safe and crucial tools to control the pandemic.…”
Section: Introductionmentioning
confidence: 94%